The issue of quality of working life of psychologists in the Unified Social Work System (Research, Society and Development, 2024)
This paper aims to provide a deeper understanding of the factors that impact the Quality of Work Life of psychologists working in the Unified Social Work System, contributing to spotting elements that can be worked on and improved in this context. This study is methodologically framed as an integrative review consisting of scientific productions from January 2015 to June 2022, targeted at discussing the quality of working life of Psychology professionals in the Unified Social Work System, especially in the Reference Centers for Social Work and Specialized Reference Center for Social Work. As a result, in 2017, 2019, 2020, and 2022, 12 papers relating to the subject were published, three in each year. In 2015 and 2016, one paper was published per year. In 2018 and 2021, four papers were published, two in each year, thus amounting to 18 papers. In the final considerations, numerous factors with the potential to influence the Quality of Working Life of Psychologists in the Unified Social Work System were evidenced. However, there are several possible interventions to treat health problems and/or as a preventive approach in relation to the well-being of people and work organizations: employee change, observation of the characteristics of an individual's work or organizational climate, change in the work environment, individual treatment, and more.